2014
DOI: 10.3109/14767058.2013.860963
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome interrogation of human myometrium identifies differentially expressed sense-antisense pairs of protein-coding and long non-coding RNA genes in spontaneous labor at term

Abstract: Objective The mechanisms responsible for normal and abnormal parturition are poorly understood. Myometrial activation leading to regular uterine contractions is a key component of labor. Dysfunctional labor (arrest of dilatation and/or descent) is a leading indication for cesarean delivery. Compelling evidence suggests that most of these disorders are functional in nature, and not the result of cephalopelvic disproportion. The methodology and the datasets afforded by the post-genomic era provide novel opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 173 publications
1
11
0
Order By: Relevance
“…This is consistent with the idea that baseline inflammation can blunt responses to stimuli (61). In fact, this could be entirely consistent with the inflammatory signatures identified in earlier studies (5,(17)(18)(19)(20)(21)(22)(23)(24), all of which were performed in the absence of an exogenous stimulus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the idea that baseline inflammation can blunt responses to stimuli (61). In fact, this could be entirely consistent with the inflammatory signatures identified in earlier studies (5,(17)(18)(19)(20)(21)(22)(23)(24), all of which were performed in the absence of an exogenous stimulus.…”
Section: Discussionsupporting
confidence: 91%
“…Transcriptomic evaluation of the uterus and fundus during labor in term and preterm birth have identified inflammatory signatures associated with labor and preterm birth (19)(20)(21)(22). Several additional studies have identified transcriptional signatures of inflammation in the placentas of women who undergo preterm delivery (23,24).…”
mentioning
confidence: 99%
“…Changes to the transcriptome of human myometrium have been demonstrated at the time of spontaneous labor, signaling a specific environment different from non-laboring myometrium. 20 Our use of wild-type mice to assess uterine contractility minimized any genetic variation that may have affected human myometrial contractility in our exploratory study. The variability in estrous phase of the mice at the time of contractility testing is a potential confounder.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its frequency and importance, there are major gaps in knowledge about the diagnosis, pathogenesis, microbiology, maternal and fetal immune response, and short-and-long term consequences of clinical chorioamnionitis, as well as optimal treatment. Systems biology can help us make major gains in the understanding of this important condition [211228]. …”
Section: Discussionmentioning
confidence: 99%